Discourse Markers Used by Presenters in Their Thesis Seminars: A Case at English Education of Graduate Program of Universitas Negeri Padang - Syafitri Ramadhani; Hermawati Syarif (Universitas Negeri Padang, 2021)
This research was aimed at finding out discourse markers used by presenters in thesis seminar presentations and oral responses in discussion sessions, difficulties faced in using discourse markers, and the causes of difficulties. The research design was descriptive qualitative with discourse analysis method with 20 graduate students that presented their thesis proposal and the research result. There were six types of discourse marker investigated in this research, namely topic change markers, contrastive markers, causative markers, elaborative markers, inferential markers and interactional markers. The research findings showed the six types of discourse markers were used in presentations and oral responses in discussions. Yet, they were mostly found in the presentations. Based on the findings, Elaborative marker is a type of discourse marker used mostly by 20 presenters in both activities. Also, it was discovered that the presenters’ difficulties in using discourse markers are difficulty to control him or herself not to keep on using the same words, phrases or sentences from each type of discourse marker in delivering utterances, underuse, overuse, and misuse of discourse markers. Those difficulties were caused by some factors such as lack of practice, the influence of mother tongue or first language and culture, and students’ awareness about the use of discourse markers. In conclusion, English graduate students still face difficulties to employ discourse markers in delivering statements.